S35 Poor influenza vaccination rates in people with airways disease. (12th November 2019) - Gates, JC; Brown, T; Heiden, E; Lodge, D; Simpson, R; Hicks, A; Rupani, H; Chauhan, AJ
Abstract : Background: NHS England recommend asthma and COPD patients receive the annual Influenza vaccination, yet uptake nationally remains low at 48% for those eligible 1 . We determined the vaccination status in patients with asthma and COPD admitted with influenza, and compared them to regional rates and investigated other aspects of their disease management, control and mortality. Methods: We interrogated primary and secondary care records of asthma and COPD patients admitted with microbiologically confirmed influenza infection between Nov 18-Apr19. We further investigated 90-day mortality, whether patients were known to secondary care, and in those with asthma, the exacerbation frequency, medication adherence and record of an annual review in the year prior to admission. Results: We identified 637 adults (≥16 years) with confirmed influenza; 196 (31%) had an existing diagnosis of asthma (102 pats, 16%) or COPD (94 pats, 15%) and records were available for 182/196 patients (93%). Only 37/95 (39%) patients with asthma and 40/87 (46%) with COPD had received the influenza vaccination. Adherence to ICS, by prescription pick-up was poor in both groups with asthma, and unvaccinated patients had significantly poorer engagement (28% vs 68% with an annual review, Fishers Exact Test p=0.002). Although not statistically significant, exacerbation frequency and 90-day mortality were higher in the unvaccinated group, and the overall mortality was 5%. The vaccination rates for both asthma and COPD patients ≥ 65 yrs and asthma patients <65 yrs were significantly lower compared to age-matched regional averages (41% and 43% vs 75% [p=0.0001] and 36% vs 52% [p=0.03] respectively). The vaccination rate was no different for those under specialist care for both asthma (32% vs 29%, p=0.82) and COPD (33% vs 23%, p=0.09). Conclusions: Asthma and COPD patients admitted with influenza had low rates of vaccination compared to the region and this was not influenced by access to specialist care. Medication adherence was poor and unvaccinated asthma patients had worse engagement and disease control. Recommendation: Opportunities to improve vaccination rates and disease control need to be explored, including vaccination at times of scheduled and unscheduled visits to both primary and secondary care. Reference: PHE: National Flu Immunisation Programme 2018